2017
DOI: 10.24326/asphc.2017.5.12
|View full text |Cite
|
Sign up to set email alerts
|

INTRODUCTION OF ENDEMIC Allium tuncelianum KOLLMAN FROM HOT AND TEMPERATE CLIMATE TO SEMI-ARID CLIMATIC CONDITIONS

Abstract: Allium tuncelianum (Tunceli garlic) is a single cloved important threatened endemic geophyte of high commercial importance that grows scattered on hot temperate mountains under oak trees in the eastern Turkish province of Tunceli. Tunceli garlic is used diversely in salads, foods and in pharmaceutical industry. They also offer a rich choice for their use in rock gardens and landscaping. There is need to develop appropriate agronomic practices for its propagation outside its habitat. In line with this objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is well known that some genotypes prefer a specific environment or are widely adapted to several environments (Thanh et al, 2016;Begna, 2020;Belay et al, 2020;Sultan & Raina, 2020;Casals et al, 2023). Nevertheless, it is also known that some garlic varieties have phenotypic plasticity in response to different environments (Volk & Stern, 2009;Kizil & Khawar, 2017;Sánchez-Virosta et al, 2021). Some studies have revealed that different agronomic responses exist in garlic varieties under various environmental factors e.g., photoperiod and temperature (Atif et al, 2019;Mathew et al, 2011), water stress (Sánchez-Virosta & Sánchez-Gómez, 2019), different fertilizer levels (Shree et al, 2014), climatic changes (Tchórzewska et al, 2017;Mahmudah et al, 2021), and planting time (Alsup-Egbers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that some genotypes prefer a specific environment or are widely adapted to several environments (Thanh et al, 2016;Begna, 2020;Belay et al, 2020;Sultan & Raina, 2020;Casals et al, 2023). Nevertheless, it is also known that some garlic varieties have phenotypic plasticity in response to different environments (Volk & Stern, 2009;Kizil & Khawar, 2017;Sánchez-Virosta et al, 2021). Some studies have revealed that different agronomic responses exist in garlic varieties under various environmental factors e.g., photoperiod and temperature (Atif et al, 2019;Mathew et al, 2011), water stress (Sánchez-Virosta & Sánchez-Gómez, 2019), different fertilizer levels (Shree et al, 2014), climatic changes (Tchórzewska et al, 2017;Mahmudah et al, 2021), and planting time (Alsup-Egbers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A. tuncelianum is considered as a vulnerable threatened plant species (Etoh and Simon 2002;Ipek et al 2008;Kizil et al 2012). This species is suitable for cultivation under eld conditions by planting bulbs gathered from nature (Kizil and Khawar 2017). However, there is no record of any breeding program aiming to develop new varieties of this species with desired agronomical traits.…”
Section: Introductionmentioning
confidence: 99%